2007
DOI: 10.1007/s11695-007-9117-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resting Energy Expenditure and Body Composition after Weight Loss following Roux-en-Y Gastric Bypass

Abstract: Background: The objective of this study was to evaluate changes in resting energy expenditure (REE), body composition and metabolic parameters, and to investigate predictors of the results in seriously obese patients after Roux-en-Y gastric bypass (RYGBP).Methods: 31 patients (BMI 44.4 ± 4.8 kg/m 2 ; 27 female, 4 male; 37.3 ± 11.1 y) were evaluated at baseline and 6 months after RYGBP. Weight, REE, waist circumference (WC), fat mass (FM) and fat-free mass (FFM), physical activity, food intake, fasting glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
86
3
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 33 publications
19
86
3
11
Order By: Relevance
“…The human literature is not entirely consistent in respect to RYGB-induced changes in overall energy expenditure (23,31,32,42,152,153). A recent review indicated that total energy expenditure in humans often decreases due to the decrease in fat-free and fat mass but that diet-induced thermogenesis is often increased (please see also below) (145).…”
Section: Energy Expenditurementioning
confidence: 99%
See 2 more Smart Citations
“…The human literature is not entirely consistent in respect to RYGB-induced changes in overall energy expenditure (23,31,32,42,152,153). A recent review indicated that total energy expenditure in humans often decreases due to the decrease in fat-free and fat mass but that diet-induced thermogenesis is often increased (please see also below) (145).…”
Section: Energy Expenditurementioning
confidence: 99%
“…The majority of data collected with the help of preclinical studies seems to be consistent with findings in humans. However, changes in energy expenditure after RYGB seem to be less consistent in humans compared with most animal models, but this may be related to the much larger heterogeneity of study populations in humans compared with laboratory animals (23,31,145,146,152).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…En este estudio, las pacientes bajaron 28,4% del peso inicial al sexto mes y 35% del peso inicial al año de la operación, cifras similares a las observadas en otros estudios 8,18,24 . La reducción de MLG correspondió a 30% del peso reducido al año postoperatorio; esta disminución es similar a la observada con tratamientos médicos 25,26 y quirúr-gicos 18,24 contra la obesidad, aunque mayor que la reportada por otros estudios 14 .…”
Section: Discussionunclassified
“…The magnitude of decreased resting energy expenditure was proportional to the postoperative weight loss. In another study, Carrasco et al 47 evaluated changes in resting energy expenditure in 31 morbidly obese patients, 6 months before and after GBP, and also found a significant reduction in resting energy expenditure. Unfortunately, the authors did not include a control group in their analysis.…”
Section: Human Studiesmentioning
confidence: 95%